Effect of Weeping Teats on Intramammary Infection and Somatic Cell Score in Dairy Goats - Gazzola, Alessandra; Minozzi, Giulietta; Biffani, Stefano; Mattiello, Silvana; Bailo, Giovanni; Piccinini, Renata (Frontiers in Veterinary Science, 2021)
Mastitis is the most common disease affecting dairy goats and causing economic losses. Although it is accepted that increased somatic cell count (SCC) is mainly a response to infection, its reliability for subclinical mastitis detection in goats is controversial. Indeed, many physiological and extrinsic variables can increase SCC, including breed, parity, age, stage of lactation, seasonal variations, and milking methods. In some animals, milk-secreting tissue is present in the wall of the teat and, in some instances, milk can filter through pores in the skin to the udder surface. This condition is known as “weeping teat” (WT). In these animals, mammary tissue might be prone to develop bacterial infections, although limited information is provided. WT seems to have a genetic background and is reported to be especially found in goat breeds selected for high milk production. Moreover, it is observed a genetic correlation between WT and decreased milk yield as well as increased somatic cell scores (SCS). Since information on this topic is very limited, this study aimed at investigating any possible relationship between WT, high SCC and the presence of bacteria in goat milk. Alpine goat farms in Northern Italy were selected based on the presence of WT. Each herd was divided into two age-matched groups, identified as case (WT+) and control (WT-). Half-udder milk samples were collected aseptically at three timepoints; bacteriological analysis was performed, and SCC were determined and transformed in somatic cell score (SCS). There was a positive association between SCS and the presence of bacteria in milk (P = 0.037) overall, whereas WT udder defect was associated with positive bacterial culture in just one herd (P= 0.053). Thus, this herd was further investigated, repeating the sampling and the analysis on the following year. The positive association between high SCS and the presence of bacteria in milk was then confirmed (P = 0.007), whereas no association with WT condition was found. These results indicate that WT defect is usually unrelated to both the outcome of milk bacterial culture and SCS. As a side outcome, we could confirme the role of bacterial infection in increasing SCS.